Close relationships in adolescents with and without a history of specific language impairment - Wadman, Ruth; Durkin, Kevin; Conti-Ramsden, Gina (American Speech-Language-Hearing Association, 2011)
Purpose: Engagement in close friendships and romantic relationships becomes particularly salient in adolescence. This study examined the influence of language, behavioral, and social variables on the level of emotional engagement experienced by adolescents with and without a history of specific language impairment (SLI). Method: Ninety adolescents with SLI and 91 adolescents with typical language abilities (TD) completed two assessment sessions between the ages of 16 and 17. Results: The group with SLI had significantly lower emotional engagement scores than the group with TD. Some 24% of adolescents with a history of SLI were judged to have poor emotional engagement in close relationships, compared to only 2% of the adolescents with typical language abilities. A regression analysis found language ability, prosocial behavior, and shyness were concurrently predictive of level of emotional engagement in close relationships. Conclusions: Some adolescents with SLI may be less emotionally engaged in their close relationships than their typically developing peers.